FAKTOR-FAKTOR YANG MEMPENGARUHI PENYAPIHAN DINI PADA BAYI 0-24 BULAN DI DESA OESUSU WILAYAH KERJA PUSKESMAS TAKARI TAHUN 2012 - BATBUAL, BRINGIWATTY (MIDWIFERY MEDICAL JOURNAL, 2014)
Background: In order to achieve growth, the first without any complementary foods and further to meet the nutritional adequacy of infants should start complementary feeding was given sufficient and safe with continued breastfeeding until the baby is 2 years old. However, there are many mothers who do weaning the baby under the age of 2 years, itâs caused the mothers lack of knowledge about howâs good, right and benefits weaning as well as the advantages of breast milk properly. In 2010 amounted to Â± 20727.2 toodler and does weaning under the age of 2 years as many as 3134 people (1.5%), while in NTT in 2010 the number of toddler, especially in the city of Kupang there are 6536 inhabitants and which do weaning under 2 years are 1473 infants (22.5%).Objective: To identify factors that influence early weaning in infants 0-24 months in the Oesusu village Puskesmas Takari.Method: This research used a descriptive study using cross sectional method. The entire population of mothers with babies 0-24 months as many as 102 people, samples taken 50 people, this study using a questionnaire.Results: The results showed that the majority of respondents, 40 respondents (80%) knowledgeable enough about the definition of early weaning, 30 respondents (60%) knowledgeable enough about the time of weaning, most respondents knowledgeable enough about how early weaning infants 0-24 month are 24 respondents (48%), 31 respondents (62%) knowledgeable enough about the effects of early weaning.Conclusion: The results of the study showed that most families have enough knowledge about the understanding, time, impact and ways good and right of weaning and most respondents are high school education.